Ethical Issues in Research Involving Children in TESOL and Applied Linguistics - Udi Samanhudi (International Journal of Language Teaching and Education, 2018)
This study sets out to address the ethical issues involved in studies concerning English language learning and acquisition which involve children (those under 18 years of age as outlined in the UN Convention on the Rights of the Child) as participants. This small-scale study focused on the analysis of ethical issues in three preliminary of samples of studies which involve children in the field of TESOL and Applied Linguistics. These three articles involved children as participants and are published in reviewed journals in the area of TESOL and Applied Linguistics. The results indicate that although implicitly presented, the informed consent and protection issues have generally been fulfilled by the researchers of the three articles. However, a more explicit explanation needs to be given more spaces in the research report in order to make it more transparent to the public (Peter, 2015; Thomas, 2009) and to ensure that the research is rigorous and significant (Dikema, 2009).